Investigation of the effect of co-axis free rotating propeller-type turbulators on the performance of heat exchanger - Durmus, A; Kurtbas, I; Gulçimen, F; Turgut, E (Pergamon-Elsevier Science Ltd, 2004)
In this study; effects of propeller-type turbulators.. which were located in the inner pipe of co-axial heat exchanger, were investigated. Propeller-type turbulators have blade angles of 10degrees, 20degrees and 40degrees, also at each angle the propeller have diameter of 48 mm, 50mm and 52 mm. This turbulators were mounted in the inner pipe by different intervals. According to the flow observing experiments, maximum decaying distance of swirl flow is 30 cm. So. experiments were done with different intervals of turbulators, which were mounted in the inner pipe of co-axial beat exchanger. In this case. beat transfer and pressure loss was investigated. Also the experiment was repeated with one turbulator mounted in the entrance of inner pipe. Then heat transfer and pressure loss was compared with each other at two cases. In the experiment, it was seen that beat transfer 2-4 times and pressure loses 8.5 times bigger than the values of empty pipe heat exchanger at Reynolds numbers of 10000-30000 and 10 different mass flow rate. (C) 2004 Elsevier Science Ltd.